2017
DOI: 10.1525/mp.2017.34.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Swing Rhythm in Classic Drum Breaks From Hip-Hop’s Breakbeat Canon

Abstract: Certain recorded drum breaks, i.e., drum patterns played without other instrumentation, have achieved iconic status, largely as a result of being frequently “sampled” in other recordings. Although these highly influential drum breaks (sometimes called breakbeats) have been integral to much of the hip-hop and other music produced in recent decades, there has been little scholarly investigation of their rhythmic features. To that end, this study examined 30 classic drum breaks from the “breakbeat canon,” focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Câmara (2016) examined excerpts from 13 funk and jazz-funk recordings (roughly 90-130 BPM), and found that drummers primarily used 16th-note swing ratios between 1.0 and 1.3. Similarly, Frane (2017) found that 16th-note swing ratios between 1.0 and 1.3 predominated among 30 classic "drum breaks" (mostly 80-100 BPM) that have frequently been sampled in hip-hop recordings. Neither Câmara nor Frane found a notable correlation between tempo and swing ratio.…”
Section: B Swing Ratios Used By Drummersmentioning
confidence: 88%
See 4 more Smart Citations
“…Câmara (2016) examined excerpts from 13 funk and jazz-funk recordings (roughly 90-130 BPM), and found that drummers primarily used 16th-note swing ratios between 1.0 and 1.3. Similarly, Frane (2017) found that 16th-note swing ratios between 1.0 and 1.3 predominated among 30 classic "drum breaks" (mostly 80-100 BPM) that have frequently been sampled in hip-hop recordings. Neither Câmara nor Frane found a notable correlation between tempo and swing ratio.…”
Section: B Swing Ratios Used By Drummersmentioning
confidence: 88%
“…Swing density is the proportion of even-numbered subdivision onsets that are overtly indicated by note onsets in a given passage (Frane, 2017). For example, in the swinging pattern shown in Fig.…”
Section: Swing Densitymentioning
confidence: 99%
See 3 more Smart Citations